Carrier detection of Duchenne muscular dystrophy in Colombia families by microsatellite analysis (2008)
Introduction: The muscular dystrophies of Duchenne and Becker are X-linked recessive neuromuscular disorders; the carrier testing protocols include mutation detection or linkage analysis. Objective: The aim of this investigation was to use the segregation analysis of STR loci to determine the carrier status in 37 families with DMD/DMB. Methods: From 37 families 174 individuals were studied through segregation of 10 intra and extragenic shorttandem repeats (STR) in the members of the family. Results: The carrier status of 89.2% women of the tested group could be assigned by linkage analysis, 65.7% carriers and 23.5% non-carriers Conclusions: Linkage analysis was proven to be a powerful tool for the carrier detection in DMD/BMD and should be taken into account in genetic counselling practice. © 2008 Corporación Editora Médica del Valle.